ELECTRICAL CONDUCTIVITY AND DIELECTRIC CONSTANT OF BENTONITE MEASURED WITH TIME-DOMAIN REFLECTOMETRY - Md. A. Mojid; Nobou Toride (Lowland Technology International, 2001)
The dielectric constant, ɛ, and bulk electrical conductivity (EC), σ, of Na- and Ca- bentonite samples were measured with time-domain reflectometry (TDR). Water retention characteristics were also determined. Na- bentonite retained much more water than Ca- bentonite at all suctions. Both bentonite pastes remained saturated for a volumetric water content Ɵ ≥ 0.60 m3 m-3 (water content by weight w ≥ 0.50 kg kg-1). The bentonite samples, athough prepared by using distilled water, had a fairly high σ with a peak at Ɵ = 0.60 m3 m-3. For saturated conditions, the EC increased with decreasing Ɵ and, hence, increasing dry bulk density, ρb. The greatest σ was found at the lowest Ɵ for which the sample was still saturated with water: σ = 3.88 dS m-1 for Na- bentonite and 1.45 dS m-1 for Ca- bentonite. The EC decreased with decreasing Ɵ for unsaturated conditions. Due to energy losses, the TDR waveform was almost completely attenuated for 0.45 ≤ Ɵ ≤ 0.87 m3 m-3 (0.31 ≤ w ≤ 2.50 kg kg-1) for Na- bentonite and for 0.36 ≤ Ɵ ≤ 0.50 m3 m-3 (0.22 ≤ w ≤ 0.38 kg kg-1) for Ca- bentonite. As the water content decreased, the quasi-crystals (tactoids), consisting of several clay particles with near-parallel alignment, came closer together and diffuse double layers started to overlap. This resulted in good conductive pathways with the greatest σ for the lowest saturated water content of Ɵ = 0.60 m3 m-3 . Additional decreased because air entered the system. The EC was higher in Na- bentonite than in Ca- bentonite for all water contents. Because of the more dispersed particles and larger number of quasi-crystal in the Na- system than in Ca- system, the electrical conductance between the quasi-crystal would be higher for the Na- bentonite than for the Ca- bentonite. Similarly, water molecules will be adsorbed more strongly and might cause higher water retention in Na- bentonite than in Ca- bentonite at the same suction.